Pseudomembranous Colitis: Not Always Caused by Clostridium difficile - Derek M. Tang; Nathalie H. Urrunaga; Hannah De Groot; Erik C. von Rosenvinge; Guofeng Xie; Leyla J. Ghazi (Case Reports in Medicine)
Although classically pseudomembranous colitis is caused by Clostridium difficile, it can result from several etiologies. Certain medications, chemical injury, collagenous colitis, inflammatory bowel disease, ischemia, and other infectious pathogens can reportedly cause mucosal injury and subsequent pseudomembrane formation. We present the case of a middle-aged woman with vascular disease who was incorrectly diagnosed with refractory C. difficile infection due to the presence of pseudomembranes. Further imaging, endoscopy, and careful histopathology review revealed chronic ischemia as the cause of her pseudomembranous colitis and diarrhea. This case highlights the need for gastroenterologists to consider non-C. difficile etiologies when diagnosing pseudomembranous colitis.